2022
DOI: 10.1002/smll.202206657
|View full text |Cite
|
Sign up to set email alerts
|

Neighboring Carboxylic Acid Boosts Peroxidase‐Like Property of Metal‐Phenolic Nano‐Networks in Eradicating Streptococcus mutans Biofilms

Abstract: Developing nature‐inspired nanomaterials with enzymatic activity is essential in combating bacterial biofilms. Here, it is reported that incorporating the carboxylic acid in phenolic/Fe nano‐networks can efficiently manipulate their peroxidase‐like activity via the acidic microenvironment and neighboring effect of the carboxyl group. The optimal gallic acid/Fe (GA/Fe) nano‐networks demonstrate highly enzymatic activity in catalyzing H2O2 into oxidative radicals, damaging the cell membrane and extracellular DNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 61 publications
1
20
0
Order By: Relevance
“…In a parallel study, TMB (12 mM) was mixed with G−Cu (50 μg/ mL) in acetate buffer solution (0.1 M, pH 4.2) containing H 2 O 2 at various concentrations (1,2,4,8,16, and 32 mM). UV−vis absorption of the resulting suspension was recorded at different time intervals on a UV-1900i spectrometer.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a parallel study, TMB (12 mM) was mixed with G−Cu (50 μg/ mL) in acetate buffer solution (0.1 M, pH 4.2) containing H 2 O 2 at various concentrations (1,2,4,8,16, and 32 mM). UV−vis absorption of the resulting suspension was recorded at different time intervals on a UV-1900i spectrometer.…”
Section: Methodsmentioning
confidence: 99%
“…Bacterial infections, especially those caused by multidrug resistant pathogens, have significantly threatened human health. , In nature, enzymes are widely involved in combating the invaded pathogens, especially in the Kingdoms Plantae and Animalia. , For example, lysozymes can induce bacterial lysis via cleavage of the peptidoglycans on the bacterial cell walls. Enzymatic cascade reactions, powered by NADPH oxidase, superoxide dismutase (SOD), and myeloperoxidase (MPO), can efficiently produce highly oxidative HOCl • to damage the bacterial cell membrane. , Although natural enzymes are selective and efficient in catalysis, they also suffer from poor thermal stability, susceptibility to proteases and pH change, and high cost-effectiveness ratio. To address the intrinsic shortcomings of natural enzymes, one promising strategy is to develop artificial enzyme mimics (AEMs). In principle, most of these AEMs possess peroxidase and oxidase activity that can boost the generation of reactive oxygen species (ROS) to damage the cell membrane, DNA, and biomacromolecules. , Several metal oxides, ions, and carbon-based nanomaterials have been developed and used as AEMs. ,, In most cases, these AEMs have a single function, used individually to catalyze reactions or in combination to achieve cascades. , Therefore, there is an urgent need to develop enzyme mimics with multiple functions to enable cascades in one system and subsequent biomedical applications.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, many researchers have deeply studied the effects of various drugs on human dental biofilm (Liu et al, 2018;Wang et al, 2023). So, we decided to further perform anti-biofilm experiments on human isolated teeth.…”
Section: Antibiofilm Activity On Ex Vivo Human Teethmentioning
confidence: 99%
“…In addition to the VDDSs mentioned above, many other types of systems, including metal–organic frameworks, dendrimers, , and microemulsions, have been used in the therapy of vaginal infections due to their unique antimicrobial activity or drug delivery performance. For example, Shi et al reported voriconazole-built metal–organic frameworks (MOFs) for eradicating C. albicans biofilms.…”
Section: Commonly Used Nanoparticles In Overcoming the Biological Bar...mentioning
confidence: 99%